Design and Development of a Novel Peptide for Treating Intestinal Inflammation - Zhang, Lulu; Wei, Xubiao; Zhang, Rijun; Petitte, Jim N.; Si, Dayong; Li, Zhongxuan; Cheng, Junhao; Du, Mengsi (Frontiers in Immunology, 2019)
Intestinal inflammatory disorders, such as inflammatory bowel disease, are associated with increased proinflammatory cytokine secretion in the intestines. Furthermore, intestinal inflammation increases the risk of enteric cancer, which is a common malignancy globally. Native anti-inflammatory peptides are a class of anti-inflammatory agents that could be used in the treatment of several intestinal inflammation conditions. However, potential cytotoxicity and poor anti-inflammatory activity have prevented their development as anti-inflammatory agents. Therefore, in this study, we designed and developed a novel hybrid peptide for the treatment of intestinal inflammation. Eight hybrid peptides were designed by combining the active centers of antimicrobial peptides, including LL-37 (13-36), YW12D, innate defense regulator 1, and cathelicidin 2 (1-13) with thymopentin or the active center of thymosin alpha 1 (Tα1) (17-24). The hybrid peptide, LL-37-Tα1 (LTA), had improved anti-inflammatory activity with minimal cytotoxicity. LTA was screened by molecule docking and in vitro experiments. Likewise, its anti-inflammatory effects and mechanisms were also evaluated using a lipopolysaccharide (LPS)-induced intestinal inflammation murine model. The results showed that LTA prevented LPS-induced impairment in the jejunum epithelium tissues and infiltration of leukocytes, which are both histological markers of inflammation. Additionally, LTA reduced the CD4+/CD8+ T lymphocyte ratio and decreased the levels of tumor necrosis factor-alpha, interferon-gamma, and interleukin-6. LTA increased the expression of zonula occludens-1 and occludin, and reduced permeability and apoptosis in the jejunum of LPS-treated mice. Additionally, its anti-inflammatory effect is associated with neutralizing LPS, binding to the Toll-like receptor 4-myeloid differentiation factor 2 (TLR4/MD-2) complex, and modulating the nuclear factor-kappa B signal transduction pathway. The findings of this study suggest that LTA may be an effective therapeutic agent in the treatment of intestinal inflammation.